IMPLEMENTATION OF KI HADJAR DEWANTARA'S PHILOSOPHY IN LEARNING TOPICS AT ISLAMIC KINDERGARTEN - Deviyanti, Novita; Priyanti, Nita (Journal of Early Childhood Education (JECE), 2022)
Children's skills become the focus in education. The concept of implementing Ki Hadjar Dewantara's philosophy in building the character and skills of 4C Creativity Thinking and innovation, Critical Thinking and Problem Solving, Communication, and Collaboration. Critical thinking is critical thinking is the process of seeking the truth in information received or in problem-solving, or it is the capacity to think abstractly by applying analysis and assessment of information received. Problem solving is a capacity to overcome any hurdles that stand in the way of your aims. Communication is an aptitude for sharing information, messages, ideas, ideas, thoughts, and feelings with others with the goal of eliciting participation; as a result, the information, messages, ideas, ideas, thoughts, and feelings become the communicator's and communicant's property. Analysis of learning topics in teaching modules aims to measure the extent to which the teaching modules used in Darul Qalam Islamic Kindergarten contain learning topics that contain the implementation of Ki Hadjar Dewantara's philosophy (kodrat zaman dan kodrat alam). This research method uses content analysis through the study of teaching modules. Content analysis is an in-depth discussion of the contents of written or printed information in the mass media symbol coding technique, namely recording symbols or messages systematically, then given an interpretation. The results of analysis kodrat alam show that there are 14 indicators, including the highest on the focus indicator (49%), and the results of the analysis of kodrat zaman, creative (50%), collaboration(32%), critical thinking(11%), communication(7%).